From Lake to River: Documenting an Environmental Transition Across the Jura/Knockfarril Hill Members Boundary in the Glen Torridon Region of Gale Crater (Mars). Issue 9 (16th September 2022) - Caravaca, Gwénaël; Mangold, Nicolas; Dehouck, Erwin; Schieber, Juergen; Zaugg, Louis; Bryk, Alexander B.; Fedo, Christopher M.; Le Mouélic, Stéphane; Le Deit, Laetitia; Banham, Steven G.; Gupta, Sanjeev; Cousin, Agnès; et al.
Abstract: Between January 2019 and January 2021, the Mars Science Laboratory team explored the Glen Torridon (GT) region in Gale crater (Mars), known for its orbital detection of clay minerals. Mastcam, Mars Hand Lens Imager, and ChemCam data are used in an integrated sedimentological and geochemical study to characterize the Jura member of the upper Murray formation and the Knockfarril Hill member of the overlying Carolyn Shoemaker formation in northern GT. The studied strata show a progressive transition represented by interfingering beds of fine‐grained, recessive mudstones of the Jura member and coarser‐grained, cross‐stratified sandstones attributed to the Knockfarril Hill member. Whereas the former are interpreted as lacustrine deposits, the latter are interpreted as predominantly fluvial deposits. The geochemical composition seen by the ChemCam instrument show K2 O‐rich mudstones (∼1–2 wt.%) versus MgO‐rich sandstones (>6 wt.%), relative to the average composition of the underlying Murray formation. We document consistent sedimentary and geochemical data sets showing that low‐energy mudstones of the Jura member are associated with the K‐rich endmember, and that high‐energy cross‐stratified sandstones of the Knockfarril Hill member are associated with the Mg‐rich endmember, regardless of stratigraphic position. The Jura to Knockfarril Hill transition therefore marks a significant paleoenvironmental change, where a long‐lived and comparatively quiescent lacustrine setting progressively changes into a more energetic fluvial setting, as a consequence of shoreline regression due to either increased sediment supply or lake‐level drop. Plain Language Summary: Between January 2019 and January 2021, the Mars Science Laboratory team explored the Glen Torridon region in Gale crater. This region is also known as the "clay‐bearing unit" after the previous observation of strong spectral signatures of such minerals from orbit. As this indicates the presence of wetter conditions during the Martian past, this area was a main objective of the mission. There, sedimentary strata show a major change from fine‐grained mudstones, characteristic of the underlying Murray formation (lake deposits), toward coarser‐grained cross‐stratified sandstones of the Knockfarril Hill member (river deposits). This change is also identified in the geochemical signal, by the ChemCam instrument. ChemCam data show higher magnesium and lower potassium in the coarse‐grained fraction compared to the fine‐grained sediment. We also observe a progressive transition with interbedding of both lithologies across the region. We interpret these strata to record a progressive transition from a quiet lake toward a more energetic lake shore to river plain, consequently to shoreline migration, due to either sedimentary fill of the basin and/or a drop in lake level. Key Points: Sedimentary facies observed by Curiosity suggest lacustrine and fluvial environments preserved in the Glen Torridon (GT) stratigraphy A paleoenvironmental transition is observed across the Jura/Knockfarril Hill members boundary, suggesting onset of fluvial conditions This transition is progressive, and consistent within both the sedimentary and geochemical signals in the GT region